1994
DOI: 10.1038/bjc.1994.257
|View full text |Cite
|
Sign up to set email alerts
|

Cancer experience in the relatives of an unselected series of breast cancer patients

Abstract: Simmary First-and second-degree relatives of an unselected series of 402 breast cancer patients have been studied for their cancer experience. In the first-degree relatives an excess of all cancers is seen [overall relative risk (RR) = 1.28, P = 0002; males RR = 1.26, P = 0.047; females RR = 1.30, P= 0.022). There is a marked excess of sarcoma (RR = 4.26, P = 0.0064); females are at high risk of breast cancer (RR = 2.68, P<0.0001) and males have an excess of carcinoma of the lip, oral cavity and pharynx (RR = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
29
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 22 publications
6
29
1
Order By: Relevance
“…Our results to date suggest that the proportion of breast cancer patients sensitive in one or more of our three assays will considerably exceed 50%. This figure is not inconsistent with recent epidemiological studies suggesting genetic predisposition, via low-penetrance genes, in a high proportion of breast cancer cases (Teare et al, 1994;Chen et al, 1995;Houlston et al, 1996). Many further studies will be required before chromosomal radiosensitivity assays could confidently be used to predict cancer predisposition in the general population.…”
Section: Cell Proliferationsupporting
confidence: 73%
See 1 more Smart Citation
“…Our results to date suggest that the proportion of breast cancer patients sensitive in one or more of our three assays will considerably exceed 50%. This figure is not inconsistent with recent epidemiological studies suggesting genetic predisposition, via low-penetrance genes, in a high proportion of breast cancer cases (Teare et al, 1994;Chen et al, 1995;Houlston et al, 1996). Many further studies will be required before chromosomal radiosensitivity assays could confidently be used to predict cancer predisposition in the general population.…”
Section: Cell Proliferationsupporting
confidence: 73%
“…As our G2 chromosomal radiosensitivity testing gave a figure for sensitivity that was some tenfold greater, we proposed the existence of other low penetrance genes that predispose to breast cancer, in addition to the A-T gene (Scott et al, 1994). Recent epidemiological studies support this view by demonstrating that the highly penetrant predisposing genes BRCAJ and BRCA2, cannot account for the overall increased risk in the relatives of breast cancer cases in general (Teare et al, 1994;Chen et al, 1995). The G2 chromosomal radiosensitivity assay requires expertise in the identification of structural chromosome changes in metaphase cells.…”
mentioning
confidence: 86%
“…Out of all BC patients, 2% have a strong genetic predisposition, caused by the highly penetrant BRCA1 and BRCA2 genes (Peto et al, 1999). Because these genes cannot account for the overall increased risk in the relatives of BC cases (Baeyens et al, 2002), it was suggested that a substantial proportion of BC patients may be predisposed to cancer through mutations in low penetrance genes (Teare et al, 1994;Roberts et al, 1999;Scott et al, 1999;Scott, 2004), which may be genes involved in DNA damage processing and repair.…”
mentioning
confidence: 99%
“…Since G 2 radiosensitivity is a feature of many inherited cancer-prone conditions such as ataxia-telangiectasia, Li-Fraumeni syndrome and hereditary retinoblastoma (reviewed in Scott et al, 1999), we proposed that G 2 sensitive breast cancer cases had an inherited predisposition to cancer, mediated through low penetrance genes, in contrast to the highly expressed genes BRCA1, BRCA2 and TP53, which confer a strong family history and account for less than 5% of all cases Ford et al, 1998). There is good epidemiological evidence for the existence of low penetrance predisposition in a substantial proportion of patients (Teare et al, 1994;Lichtenstein et al, 2000;Peto and Mack, 2000).…”
mentioning
confidence: 99%